2022
DOI: 10.3390/jrfm15030127
|View full text |Cite
|
Sign up to set email alerts
|

Responses of the International Bond Markets to COVID-19 Containment Measures

Abstract: Using an international sample during the COVID-19 outbreak, our study gives evidence that COVID-19 containment measures impact volatility in the international bond markets in different ways. We found that the positive effect of increasing new COVID-19 vaccinations markedly mitigates bond market volatility, while non-pharmaceutical government interventions resembling bad news increase volatility in bond markets. Besides this, changes in total COVID-19 cases and total deaths have co-movement and a significant re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
1
5
1
Order By: Relevance
“…This study is in line with the results of research by To et al, (2022) 2021), shows the results that countries affected by Covid 19 are very strong, such as Italy, which has more stable yields than countries that are not as bad as Italy. This result also supported by Retnoningsih and Naufa (2021) showed that Covid 19 especially the new death has the biggest influence on the capital market.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study is in line with the results of research by To et al, (2022) 2021), shows the results that countries affected by Covid 19 are very strong, such as Italy, which has more stable yields than countries that are not as bad as Italy. This result also supported by Retnoningsih and Naufa (2021) showed that Covid 19 especially the new death has the biggest influence on the capital market.…”
Section: Discussionsupporting
confidence: 92%
“…The majority of research on the impact of Covid 19 in Indonesia is carried out on the capital market or financial performance, no one has tried to test research on bonds, especially government bonds. Research on government bonds, which is an important part of global trading, is still rare (To et al, 2022). Even though, the study of government bond yields is very crucial from a capital markets perspective, it affects investors' returns and portfolio rebalancing strategies (Papavassiliou, 2021).…”
Section: Figure 1 Comparative Government Bonds Yield-tenor 10mentioning
confidence: 99%
“…Recent studies have focused on emerging markets to analyse the impact of the COVID-19 crisis in different contexts and frameworks (e.g., Gubareva, 2021 ; Haroon and Rizvi, 2020a ; Topcu and Serkan, 2020 ; Janus, 2021 ; Xu and Lien, 2021 ; Zaremba et al, 2021 ; Bȩdowska-Sójkaa and Kliber, 2022 ; To et al, 2022 ). For example, Gubareva ( 2021 ) analyses bond market liquidity in emerging countries during the COVID-19 crisis and finds that liquidity has been severely damaged, with values far removed from pre-COVID-19 levels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They find that the more restrictions, the higher the volatility and the wider the sovereign bond spread. A recent study by To et al ( 2022 ) also explores the impact of containment measures during the COVID-19 pandemic on different emerging and developed bond markets, including the BRICS, highlighting the importance of mass vaccination.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The key independent variables are proxied to examine the effects of people vaccinated, stringency measures, and the government’s response to stock market volatility. In our study, these variables include the vaccine initiation rate ( ) measured as the number of new COVID-19 vaccines divided by the entire population; the daily relative change 3 of the Oxford Covid-19 Government Response Tracker index ( ) [ 21 , 35 ]; and the relative daily change of COVID-19 total cases and fatalities per million people [ 7 , [9] , [10] , [11] , [12] ].…”
Section: Methodologiesmentioning
confidence: 99%